Improving indoor coverage by channel reuse in two-tier femtocell networks - Wong, Yi Lin (2016)
In recent years, the growth of better-quality smartphones has encouraged the increased use of mobile communication through their hand-held devices. Users can communicate with their family members and friends, surf the Internet for checking emails and staying updated with latest news or entertainments. This growth of data traffic leads to a high demand in better quality of service (QoS) and network coverage. One of the ways to improve the indoor network coverage is by adopting femtocell base stations. Femtocell is a mini base station that is deployed to improve the indoor network coverage. It allows users to have high-speed data connection where the macrocell could not deliver. This project aims to study how indoor coverage can be improved through the implementation of femtocell in the existing macrocell network. Studies of the 3 types of path-loss model are presented and are simulated via MATLAB programming. The first type of the path-loss model is the urban micro model where path loss is measured outdoors; the second model is the indoor hotspot model where users are in an indoor environment and, lastly, the outdoor-to-indoor model where users are in an indoor environment but receiving and transmitting from an outdoor base station. Different system models such as macrocell system model and femtocell system model will be implemented to analyze the impact of co-tier and cross-tier interference. To improve network capacity, two methods will be implemented into the system model. The two methods are the frequency reuse scheme and the resource partitioning scheme. In the frequency reuse scheme, the frequency band of each base station can be reused with other further distanced base stations, thus achieving higher network coverage. In resource partitioning, femtocell will reserve its frequency band for outdoor users to prevent interference with its own indoor users. Analysis on how interference can be reduced or eliminated after the implementation of these two schemes will be made. With the improved models, mobile users will be able to receive good QoS and better network coverage no matter they are in an outdoor or indoor environment. Last of all, recommendations will be proposed to suggest how improvement can be made in this research project.